2019
DOI: 10.1002/jmv.25618
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and functional implication of HPV16 from cervical intraepithelial neoplasia in Shanghai women

Abstract: Human papillomavirus (HPV)16 gene mutation is usually associated with persistent HPV infection and cervical intraepithelial neoplasia (CIN). However, the functional implications of HPV16 mutations remain poorly understood.145 LCR/E6/E7 of the HPV16 isolates were amplified and sequenced, and HPV16 integration status was detected. In total, 89 SNPs (68 in the LCR, 13 in E6, 8 in E7) were discovered, 11 of which were nonsynonymous mutations (8 in E6, 3 in E7). The H85Y and E120D variants in E6 were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
4
5
0
Order By: Relevance
“…The viral E2 protein is known to bind as a dimer to the LCR recognition sites and regulate the expression of E6 and E7 genes [41], and variation G7004A/C might impact the binding efficiency of the viral E2 protein to the LCR. It is noteworthy that none of our samples showed variations in the YY1 binding site that are reported to impact the overexpression of viral oncogenes and tumour progression [16,20,33,42]. Similarly, previous studies have also reported variations in viral and cellular TFbs in HPV16 LCR from Europe, Thailand, and PR China [9,16,31,33,43,44].…”
Section: Lcr Variationssupporting
confidence: 64%
See 2 more Smart Citations
“…The viral E2 protein is known to bind as a dimer to the LCR recognition sites and regulate the expression of E6 and E7 genes [41], and variation G7004A/C might impact the binding efficiency of the viral E2 protein to the LCR. It is noteworthy that none of our samples showed variations in the YY1 binding site that are reported to impact the overexpression of viral oncogenes and tumour progression [16,20,33,42]. Similarly, previous studies have also reported variations in viral and cellular TFbs in HPV16 LCR from Europe, Thailand, and PR China [9,16,31,33,43,44].…”
Section: Lcr Variationssupporting
confidence: 64%
“…It is noteworthy that none of our samples showed variations in the YY1 binding site that are reported to impact the overexpression of viral oncogenes and tumour progression [16,20,33,42]. Similarly, previous studies have also reported variations in viral and cellular TFbs in HPV16 LCR from Europe, Thailand, and PR China [9,16,31,33,43,44]. Several single and cooccurring variations have been characterized in Indian isolates of HPV16 and their correlation with disease grade status has been studied.…”
Section: Lcr Variationssupporting
confidence: 61%
See 1 more Smart Citation
“…Many HPV intratype variants have been isolated in various clinical studies and a careful classification of variants of the most frequent HPV types in cancer has been achieved [ 9 , 15 , 17 ]. It has been postulated that nucleotide variations that occur among HPV intratype variants are reflected in functional differences and in their pathogenicity [ 18 , 19 , 20 , 21 ]. Currently, there are many studies that report that HPV-16 and -18 intratype variants differentially alter host cells, which translates into different risks of persistence and progression to cancer [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other authors show that the biomarkers Ki67 and TP53 are also considered to be a marker of high oncogenic Papillomavirus infection in intraepithelial neoplasia of the cervix [21][22][23]. Further research is focusing on identification of viral oncopreteins E6 and E7 as markers of high-risk Papillomavirus infection in intraepithelial neoplasia [24][25][26]. PD-L1 is involved in the molecular mechanism of cervical carcinogenesis by resistance to anti-tumor immunity of intraepithelial neoplasia cells [27,28].…”
Section: Introductionmentioning
confidence: 99%